Criminal Podcast in Polish as a Foreign Language Classes - Bursiak, Marta (Activation – innovation – acculturation. (Glotto)didactics and the migration crisis, 2024)
The main purpose of this article is to discuss the potential of Polish crime podcasts as activating, innovative and effective teaching tools in Polish as a foreign language lessons. The study distinguishes individual stages of preparing a podcast for use in a lesson and presents suggestions for exercise techniques that can be performed during its various phases. The representative research material was a crime podcast entitled: Where is Al Bano and Romina Power’s daughter? from the Kryminatorium channel available on YouTube. This particular type of text, arising from forensic discourse, was analyzed in accordance with the assumptions of the glottodidactic methodology. On its basis, concepts of sample tasks (mainly lexical) for the selected podcast were presented. The linguistic analysis of the material shows that crime podcasts can support the development of various linguistic skills and subsystems. However, they must be properly prepared methodically and enriched with exercises illustrating and developing selected lexical and grammatical issues.